PENERAPAN PROGRAM UNGGULAN RINTISAN BOARDING SCHOOL DALAM MEMBENTUK KARAKTER SISWA MADRASAH IBTIDAIYAH - Annisa Fajriatul Awwaliyah; Elya Umi Hanik; Syaiful Anam (Universitas Islam Malang, 2023)
This study aims to clearly determine: 1) The implementation of the Pioneer Boarding School Program in shaping the character of MI NU Miftahul Huda 02 Gebog Kudus students, 2) The success of the Pioneer Boarding School Program in shaping the character of MI NU Miftahul Huda 02 Gebog Kudus students. This research is a qualitative descriptive study conducted using a field research approach, Data collection techniques included interviews, observations, and documentation. The results of the study indicate that The results of the study indicate that: 1) Boarding School Program in shaping the character of students involves several steps, including the planning phase, and then the implementation, The third phase is evaluation. 2) The success of implementing the Pioneer Boarding School Program in shaping the character of MI NU Miftahul Huda 02 Karangmalang Gebog Kudus students lies in integrating moral knowing, moral feeling, and moral behavior in combining academic and religious character education. This program has been successful in integrating academic and religious character education through classroom-based character education and madrasah-based cultural character education, as evidenced by the improvement of students' disciplined, independent, responsible, and environmentally conscious character. Â